181 Impact of leaflet-tethering angle correction on the assessment of tricuspid regurgitation severity using the PISA method. (8th December 2021) - Tomaselli, Michele; Gavazzoni, Mara; Muraru, Denisa; Caravita, Sergio; Volpato, Valentina; Oliverio, Giorgio; Ciambellotti, Francesca; Rella, Valeria; Heilbron, Francesca; Menè, Roberto; Cascella, Andrea; Ciampi, Pellegrino; et al.
Abstract: Aims: Severe tricuspid regurgitation (TR) is associated with excess mortality and morbidity. Therefore, accurate assessment of TR severity is pivotal. In clinical routine, the calculation of the effective regurgitant orifice area (EROA) and the regurgitant volume (RVol) using flow convergence method (PISA) by echocardiography are among the recommended parameters to define TR severity. However, the distortion of the proximal convergence zone related to the extent of valve leaflet tethering may result in smaller PISA radius and in underestimation of TR severity. Correcting for the angle of the leaflet tethering could reduce errors due to geometric assumption of a flat valvular plane and improve the accuracy of the calculations. The aims of our study were: (1) to evaluate whether taking into account the extent of leaflet tethering by applying the angle correction (AC) in the PISA formula improves the accuracy of the quantitative assessment of TR severity; (2) to assess the potential clinical impact of AC. Methods and results: Forty-one patients with functional TR (73.5 ± 11.8 years, 51% men, 36% sinus rhythm, 17% severe), underwent 2D and 3D echocardiography. We compared the RVol obtained by volumetric method (as reference) with the RVol by PISA with and without AC. TR RVol by volumetric method was calculated as: total RV stroke volume (RV SV)–left ventricular forward SV (LV SV), where RV SV was obtained by subtracting the end-systolic from end-diastolic RV volume measured by 3D echocardiography and LV SV was calculated by multiplying LV outflow area by velocity time integral (VTI). TR RVol by PISA was calculated as EROA × VTI TR. Uncorrected EROA was calculated using the formula: 6.28 r 2 × Va/PeakV TR ( r —PISA radius, Va, aliasing velocity, PeakV TR—TR peak velocity). The corrected EROA accounting for the PISA geometric distortion by leaflet tethering angle ( α ) was calculated as: 6.28 r 2 × Va ( α /180)/PeakV TR (PISAAC ), where α was measured using a protractor generated by dedicated software. PISA radius and angle were 5.5 ± 1.97 mm and 211.2° ± 13.6°, respectively. Application of AC to PISA method resulted in larger EROA and RVol (0.34 ± 0.38 cm 2 vs. 0.24 ± 0.24 cm 2 and, 25.2 ± 19.3 ml vs. 18.6 ± 13.1 ml, respectively). The percentage change in EROAAC was over 40%. When compared to the volumetric method, RVol by corrected PISA method was significantly closer and correlated (bias −3.95 ml, LOA ± 6.41 ml, r = 0.987; P < 0.001) than the conventional PISA without AC (bias −10.5 ml, LOA ± 15 ml, r = 0.975). Angle correction resulted in a change of TR severity in 32% of cases and in a greater concordance of TR severity grade with the volumetric method (75%, 31/41 with AC vs. 52%, 22/41 without AC). Conclusions: Angle-corrected PISA method that accounts for the extent of the leaflet tethering in TR provided significantly larger TR RVol that were closely correlated with the volumetric RVol by 3D echocardiography. A simple geometric angle correction of the proximal flow with PISA method reclassified up to one-third of patients with functional TR.